Ratscalibur - Lieb, Josh; Lintern, Tom (New York, New York : Razorbill, an imprint of Penguin Group (USA), 2015)
"When Joey is bitten by a rat, he goes from aspiring seventh-grader to three-inch tall rodent, and unwittingly unlocks the sword Ratscalibur"--
Keywords: Rats -- Juvenile fiction; Magic -- Juvenile fiction; Heroes -- Juvenile fiction; Prophecies -- Juvenile fiction; Rats -- Fiction; Magic -- Fiction; Heroes -- Fiction; Prophecies -- Fiction